2003
DOI: 10.1128/jb.185.1.340-348.2003
|View full text |Cite
|
Sign up to set email alerts
|

Forespore-Specific Expression ofBacillus subtilis yqfS, Which Encodes Type IV Apurinic/Apyrimidinic Endonuclease, a Component of the Base Excision Repair Pathway

Abstract: The temporal and spatial expression of the yqfS gene of Bacillus subtilis, which encodes a type IV apurinic/ apyrimidinic endonuclease, was studied. A reporter gene fusion to the yqfS opening reading frame revealed that this gene is not transcribed during vegetative growth but is transcribed during the last steps of the sporulation process and is localized to the developing forespore compartment. In agreement with these results, yqfS mRNAs were mainly detected by both Northern blotting and reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…ExoA, much like E. coli XthA, possesses AP endonuclease, 3=-5= exonuclease, and 3=-phospho-monoesterase activities (378). Surprisingly, an exoA yqfS double mutant fails to display a reduction in tolerance to AP sites, and its mutation frequency does not increase, suggesting that another AP endonuclease may be present in B. subtilis (424).…”
Section: Processing Of Apurinic/apyrimidinic Sitesmentioning
confidence: 96%
See 1 more Smart Citation
“…ExoA, much like E. coli XthA, possesses AP endonuclease, 3=-5= exonuclease, and 3=-phospho-monoesterase activities (378). Surprisingly, an exoA yqfS double mutant fails to display a reduction in tolerance to AP sites, and its mutation frequency does not increase, suggesting that another AP endonuclease may be present in B. subtilis (424).…”
Section: Processing Of Apurinic/apyrimidinic Sitesmentioning
confidence: 96%
“…In addition, His 6 -YqfS protein is detected in mature spores, suggesting that this protein could repair AP sites during spore germination (339). In contrast to E. coli nfo, yqfS is not induced by the presence of superoxide radicals, which are generated following challenge of cells with paraquat and hydrogen peroxide (424). B. subtilis also has an AP endonuclease gene of the exonuclease III class, called exoA, which is conserved throughout biology, with members including E. coli xthA and human APEX1 and APEX2.…”
Section: Processing Of Apurinic/apyrimidinic Sitesmentioning
confidence: 99%
“…Except for the loop sequence, the complementary sequence on the opposite strand is identical to the yqfT terminator. However, a Northern blotting experiment [27] revealed that yqfS and yqfU are transcribed together. Hence, the stem-loop structure terminates transcription on the forward strand, but not on the reverse strand, in spite of the similarity of the stem-loop structure and T-stretch on the two strands.…”
Section: Position Of Transcriptional Terminators In B Subtilismentioning
confidence: 99%
“…An important function of the s G regulon lies in spore protection. This is evidenced by the s G -dependent transcription of the splB gene, encoding a spore photoproduct lyase (Fajardo-Cavazos & Nicholson, 2000;PedrazaReyes et al, 1997), and yqfS, encoding a type IV apurinic/ apyrimidinic endonuclease (Urtiz-Estrada et al, 2003). The SASP proteins, some of which bind to the DNA and participate in resistance to heat, UV radiation and desiccation, are abundant spore proteins (Setlow, 1995).…”
Section: Differentiation Of the Compartment-specific Sporulation Regumentioning
confidence: 99%